Identification of Type I IFN in Chinese giant salamander (Andrias davidianus) and the response to an iridovirus infection. Issue 2 (June 2015) - Chen, Qian; Ma, Jie; Fan, Yuding; Meng, Yan; Xu, Jin; Zhou, Yong; Liu, Wenzhi; Zeng, Xianhui; Zeng, Lingbing
Highlights This is the first report of the identification and characterization of typeIIFN in the Chinese giant salamander. Identification of the C-terminal CAWE motif in Chinese giant salamander typeIIFN. Chinese giant salamander typeIIFN was significantly induced by poly I:C and giant salamander iridovirus (GSIV) infection in peripheral blood leucocytes. The in vitro anti-viral function of the Chinese giant salamander typeIIFN was demonstrated for the first time.